People with diabetes foot complications do not recall their foot education: a cohort study - Julia Yuncken; Cylie M. Williams; Rene Stolwyk; Terry P. Haines (Journal of Foot and Ankle Research, 2018)
Abstract Background The purpose of this study is to document what and how diabetes specific foot health information was provided during a podiatry consultation, and what information was retained at 1 month post consultation. Methods This project was embedded within a prospective cohort study with two groups, podiatrists and people with diabetes. Data collection included the Problem Areas in Diabetes Questionnaire (PAID), Montreal Cognitive Assessment (MoCA), information covered during the consultation, method of delivery and perceived key educational message from both participant perspectives at the time of the appointment and 1 month post appointment. Results There were three podiatrists and 24 people with diabetes who provided information at the two time points. Diabetes education provided by the podiatrists was mostly verbal. The key educational message recalled by both groups differed at the time of the appointment (14 out of 24 of responses) and at 1 month post the appointment time (11 out of 24 of responses). Conclusions Education is a vital component to the treatment regime of people with diabetes. It appears current approaches are ineffective in enhancing understanding of diabetes impact on foot health. This study highlights the need for research investigating better ways to deliver key pieces of information to this population.